Examination of the effectiveness of the independent investigative panel 2020 in addressing police brutality in Nigeria - Probert, Thomas (University of Pretoria, 2023)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.